Numerical Modeling of Thermodynamical and Microstructural Parameters of Convective Clouds in the Process of Their Evolution - Ashabokov, B. A.; Shapovalov, A. V.; Shapovalov, V. A.; Guchaeva, Z. Kh (Journal of mathematical sciences (New York, N.Y.), 2021)
In this paper, a three-dimensional, nonstationary numerical model of convective clouds is presented. Hydrothermodynamical, microphysical, and electrical processes are described in detail; results of studies of changes in thermodynamical, microstructural, and electrical parameters in time are given. The hydrothermodynamical block of the model consists of equations of motion that describe the wet convection in the Boussinesq approximation. The equations of the microphysical block describe the processes of nucleation, condensation, coagulation, sublimation, accretion, aggregation, and freezing of drops, deposition of cloud particles in the gravity field, their transport by air flows, and interaction of cloud particles under the influence of electric fields of clouds. Numerical experiments based on the model developed were carried out to study the formation of convective clouds for various stratifications of the atmosphere and the structure of the wind field in the atmosphere. Thermodynamical and microstructural parameters in the zone of a powerful convective cloud are determined. The system of equations of the model was solved by the methods of splitting in physical processes and component-wise splitting.